Rawls on agreeing to disagree: How democracies differ from non-democracies in justifying war. Issue 1 (2nd January 2018) - Kapust, Daniel; Nelson, Travis; Robiadek, Katherine M.
ABSTRACT: We use Rawls's account of public reason and the Law of Peoples to test two hypotheses: democracies are more likely to invoke self-defense in justifications than non-democracies, and democracies are more likely to invoke human rights in justifications than non-democracies. Through an analysis of war justifications since 1875, we find that although democracies and non-democracies are similarly likely to use self-defense as a justification, democracies are more likely to justify war through human rights. Institutions and values centering on rights that promote domestic public justification also promote justifications compatible with those values and institutions at the international level.